2017
DOI: 10.1002/ejic.201601345
|View full text |Cite
|
Sign up to set email alerts
|

Iron(II) and Zinc(II) Complexes with Tetradentate Bis(pyrazolyl)methane Ligands as Catalysts for the Ring‐Opening Polymerisation of rac‐Lactide

Abstract: A new subgroup of bis(pyrazolyl)methane ligands has been developed through the synthesis of the first N,N,N,Ntetradentate bis(pyrazolyl)methane compounds, namely, bis-(pyrazolyl)bipyridinylmethane [HC(Pz) 2 Bipy, L1] and bis(3,5methylpyrazolyl)bipyridinylmethane [HC(3,5-MePz) 2 Bipy, L2].From these ligands, a large variety of new mononuclear Fe II and Zn II complexes with counterions ranging from halides to carboxylates and sulfate were synthesised and characterised by [a]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
41
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 84 publications
0
41
0
1
Order By: Relevance
“…The three hybrid guanidines werer eactedw ith iron(II) chloride, and the molecular structures of the complexes [FeCl 2 (TMGqu)] (1), [FeCl 2 (TMGasme)] (2), and [FeCl 2 (TMG5NMe 2 asme)] 2 (3)w ere determined by single-crystal XRD (Figure 1a nd Ta ble 1). 4 and 5 have been reported to be the fastestk nown robust catalysts with ab iocompatible metal for the polymerization of LA [20] but they werea lso surpassed by 2 and 3.A lthough iron catalyst have often been slower than the equivalent zinc catalysts, [16] our study shows for the first time that by simply changing the metal center in the complex from zinc to iron the polymerization activity is enhanced by af actor of five. [18] All complexes have at etra-coordinated iron center with coordination by the two donors of the hybrid guanidinel igand and two chloride ions.…”
mentioning
confidence: 63%
See 3 more Smart Citations
“…The three hybrid guanidines werer eactedw ith iron(II) chloride, and the molecular structures of the complexes [FeCl 2 (TMGqu)] (1), [FeCl 2 (TMGasme)] (2), and [FeCl 2 (TMG5NMe 2 asme)] 2 (3)w ere determined by single-crystal XRD (Figure 1a nd Ta ble 1). 4 and 5 have been reported to be the fastestk nown robust catalysts with ab iocompatible metal for the polymerization of LA [20] but they werea lso surpassed by 2 and 3.A lthough iron catalyst have often been slower than the equivalent zinc catalysts, [16] our study shows for the first time that by simply changing the metal center in the complex from zinc to iron the polymerization activity is enhanced by af actor of five. [18] All complexes have at etra-coordinated iron center with coordination by the two donors of the hybrid guanidinel igand and two chloride ions.…”
mentioning
confidence: 63%
“…[6] The industrially used catalyst for the polymerization of LA is tin(II)octanoate [Sn(Oct) 2 ]w ith alcohol as co-initiator;h owever,w hile the polymer degrades, tin residues accumulate in the environment (e.g.,t hrough industrial composters). [16] Here, we presentt he first robust complexes with a biocompatible metal that are more active in the polymerization of LA than Sn(Oct) 2 . [6a, 8] Ah uge variety of catalysts are already known for the ROP of LA.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…[3] The metal-mediated ring-opening polymerization (ROP) of lactides and lactonesi s, nowadays, the most efficient catalytic process for APEs production. Fe complexes activei nt he ROP of cyclic esters are limited, [11][12][13][14][15][16][17][18][19][20][21][22][23] and no examples have been reported that produce cAPEs. [5] Amongo thers, polymers with ac yclic topologya re an intriguing synthetic target because the lack of chain-ends and the high conformational constraintl ead to materialp roperties that are different from their linear analogues.…”
mentioning
confidence: 99%